Perspectives of health workers on malaria case referral among pregnant women attending antenatal care in Savelugu Municipality, Ghana: A qualitative descriptive study - Martin Nyaaba Adokiya (PLoS ONE, 2025)
Background Malaria remains endemic in Africa, with pregnant women exposed to the dangers of complications, which require emergency referral for lifesaving interventions. This study explored the perspectives of health workers on malaria case referral among pregnant women attending antenatal care (ANC) at health facilities in Savelugu Municipality, northern Ghana. Methods The study employed a qualitative descriptive design with a constructivist grounded theory perspective. A semi-structured interview guide was used to collect information from thirteen health workers on face-to-face. The participants were purposefully sampled and interviewed. The data were transcribed verbatim. Content analysis was performed and the results were presented as themes and sub-themes. Results After the analysis, two main themes and six sub-themes emerged from the data: a robust referral system (patient awareness and consent, documentation, referral coordination, and post-referral feedback) and a referral mechanism (ambulance/nurse accompaniment, and transportation shortfalls/patients left to their fate). Participants described the referral system as robust but reported transport challenges as the main obstacle to its operation. The study also revealed that health workers do not accompany all referral cases. Conclusion A referral system exists in the Savelugu Municipality with transportation lapses causing delays. Health workers often failed to accompany referred cases to the referral facilities. Though an inter-sectoral approach is needed to tackle the referral transport challenges, facility managers need to ensure that all referred cases are accompanied by a designated health worker.